Pembuatan lip balm nanoekstrak umbi bit (Beta vulgaris L.) dan bunga rosella (Hibiscus sabdariffa L.) sebagai pelembab alami - Jannah, Miftahul; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari; Rani , Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
One of the most sensitive parts of the outer skin on the face is the lips, as they are prone to extreme weather conditions such as heat and cold, which can cause dryness and chapping. To address this condition, it is essential to use a lip balm. One of the plants used as an active ingredient in lip balm formulations is beetroot and rosella flower. Nanoparticle-based cosmetics have advantages over micro-scale cosmetics. The objective of this research was to determine whether nano extracts of beetroot and rosella flower can be formulated into a lip balm preparation, whether beetroot and rosella flower extracts meet the characteristic requirements as nano extracts, and whether lip balm formulations from beetroot and rosella flower can be used as moisturizers. This research method is true experimental with a post-test control group design, where the results were observed after the treatment. The study uses samples of beetroot and rosella flowers. The stages of this research include sample preparation, characterization of simplicia, phytochemical screening, extraction and nano-extraction, lip balm formulation, physical quality evaluation, and moisture testing. The research results show that beetroot and rosella flower contain alkaloids, flavonoids, saponins, tannins, and anthocyanins. The beetroot and rosella flower extracts meet the characteristics of nanoextracts, with particle sizes of 261.64 nm for beetroot and 143.86 nm for rosella flowers. Beetroot and rosella flower formulated into a lip balm preparation can moisturize the lips, as evidenced by increased moisture and oil content on the lip skin before and after the preparation.